Assessment of Vitamin D Level in Patients with Psoriasis and Its Correlation with Disease Severity: A Case–Control Study - Pokharel R; Agrawal S; Pandey P; Lamsal M (Dove Medical Press, 2022)
Ranju Pokharel,1 Sudha Agrawal,1 Prajwal Pandey,1 Madhab Lamsal2 1Department of Dermatology and Venereology, B.P Koirala Institute of Health Sciences, Dharan, Nepal; 2Department of Biochemistry, B.P Koirala Institute of Health Sciences, Dharan, NepalCorrespondence: Ranju Pokharel, Junior Resident, Department of Dermatology and Venereology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal, Tel +9779860660852, Email ranjupokharel.rp@gmail.comBackground: Chronic plaque psoriasis is a chronic inflammatory skin disorder. Vitamin D has been shown to have effects on keratinocyte differentiation as well as immune regulation in the skin.Objective: The main objective of this study was to assess the 25hydroxyvitamin D [25 (OH) D] level in patients with psoriasis in comparison with healthy control subjects.Materials and Methods: This case-control study included 180 persons (120 cases and 60 age- and sex-matched control subjects) from outpatient department of BPKIHS, a tertiary care hospital in eastern Nepal. Severity of psoriatic skin lesions was assessed using psoriasis area severity index (PASI) scoring. Serum vitamin D level was assessed by chemiluminescent immunoassay.Results: The mean serum 25(OH) D levels in psoriatic patients and controls were 19.57 ± 6.85 ng/mL and 23.63 ± 6.40 ng/mL, respectively. The difference was statistically significant even after adjusting for confounding factors in a multivariate analysis (aOR 2.929, 95% CI 1.376- 6.230). Low serum 25(OH) D levels were negatively associated with the severity of disease (r= − 0.628, P= 0.01).Conclusion: Serum 25(OH) D levels are significantly lower in psoriatic patients than in healthy control subjects. Deficiency of serum 25(OH) D was associated with severity of disease with an inverse relationship with PASI score.Keywords: psoriasis, psoriasis area severity index, 25hydroxyvitamin vitamin D